Genetic dissection of auxin regulated root development - Rashed, Afaf Abdullah (2017)
As plants are sessile organisms, their developmental plasticity is crucial for adapting to environmental signals. Plant roots play a key role foraging resources in the soil to facilitate uptake of water and nutrients. The plant hormone auxin is a critical regulator of root growth and development, controlling root hair, branching and root angle. This thesis investigates the function of several auxin-regulated genes that control different aspects of root growth and development. It is important to maintain an appropriate auxin level in plant tissues by regulating auxin biosynthesis, transportation, conjugation and degradation pathways. In Arabidopsis thaliana, the DIOXYGENASE FOR AUXIN OXIDATION 1 (AtDAO1) gene has recently been identified to have a major function in regulating the oxidation of IAA to oxIAA. Metabolic profiling data of Atdao1 mutant lines identified that IAA level remains similar to wildtype in contrast to oxIAA and IAA congregates, revealing IAA degradation acts redundantly with the conjugate machinery. In addition, close examination of dao1 loss of function lines revealed several auxin-related phenotypes including the lengths of primary roots and root hairs. Auxin also plays a key role during lateral root branching. Bioinformatic analyses of a lateral root transcriptomic time course identified LATERAL ROOT KINASE 1 and 2 (LRK1 and LRK2, two putative LRR kinases) that exhibit the same expression dynamics during early stages of lateral root development as the auxin regulated transcription factor GATA23 that controls lateral root founder cell priming. lrk mutant analysis revealed that LRK1 and LRK2 function to controllateral root initiation. Reporter studies identified LRK1 and LRK2 are induced in root endodermal cells in the elongation zone, suggesting these genes regulate lateral root initiation indirectly. Auxin also regulates root angle. Transcriptomic profiling of a gravitropic auxin mutant arf7 arf19 identified 195differently expressed genes regulated by auxin and ARF7 ARF19. Reverse genetic studies characterised several candidates AT2G25900 (Cys3His transcription factor, TF) and AT5G47540 putative Mo25-like protein have been characterized to have function in root gravity response. Several experiments have been performed on several independent knock-out alleles to investigate the expression pattern of these two genes. The phenotyping results showed no significant differences in response to gravity stimulus, despite the original MO25 allele (mo25-2) exhibiting a strong lateral root phenotype.